PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS SQ3R DAN WEB PADA MATERI SISTEM PERTAHANAN TUBUH DAN PENGARUHNYA TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI MAS JEUMALA AMAL LUENG PUTU PIDIE JAYA - Havea Juliar Apko; Hasanuddin Hasanuddin; Ismul Huda (Universitas Islam Negeri Ar-Raniry, 2017)
The aim of this study is to find out the effect of the development of learning tools through a web-based SQ3R strategy to the improvement of students’ learning motivation in the concept of defense system of the body at class XI of MAS Jeumala Amal of Pidie Jaya (a private Senior High School). The data were collected from April 4th to May 11th, 2016 in the even semester of the school year 2015-2016. A quasi-experimental method is implemented with qualitative and quantitative approach. This study was conducted in four classes. Two classes were chosen for experimental class which consisted of 30 male students of IPA 3 and 30 female students of IPA 6. Meanwhile, two other classes were chosen as control class, they were 30 male students of IPA 1 and 30 female students of IPA 4. The instrument used was learners’ motivation questionnaire. The data were analyzed by using Kruskal-Wallis test with SPSS 17.0 for Windows at significant level of 0.05. The Chi-test results showed that the P-value < critical limit in which learning motivation was 0.000